2018
DOI: 10.1177/0042098018783870
|View full text |Cite
|
Sign up to set email alerts
|

Identification and quantification of urban space in India: Defining urban macro-structures

Abstract: Urban–rural differences seem particularly pronounced in India, especially when based on the official figures provided by the Census of India, which are heavily dependent on the administrative status of settlements. India, one of the world’s most dynamic and populous countries, still possesses an official urbanisation rate lagging well behind other developing economies. To investigate the extent of Indian urbanisation, this article develops a multi-step methodology using indicators specifically conceived for id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Chandrashekar (2011) found that 8 million rural residents travelled routinely to work in urban centres across India in 2009–2010, constituting about 9% of the urban workforce. The article by Perez et al (2019, this volume) exemplifies this project of proposing more sensitive ways to capture India’s urbanisation processes by employing alternative methods…”
Section: The Vsimentioning
confidence: 99%
“…Chandrashekar (2011) found that 8 million rural residents travelled routinely to work in urban centres across India in 2009–2010, constituting about 9% of the urban workforce. The article by Perez et al (2019, this volume) exemplifies this project of proposing more sensitive ways to capture India’s urbanisation processes by employing alternative methods…”
Section: The Vsimentioning
confidence: 99%
“…A first series of morphological closings, parametrized according to the detected threshold value, are produced on the centroid distributions {B i ( k )} and {B i ( k + x )}. These morphological closings, like the ones applied in Perez et al. (2019b), are composed of a dilation followed by an erosion algorithm.…”
Section: Morphological Closings Experimental Variograms and Classification Of Residential Buildingsmentioning
confidence: 99%
“…Offsets around the 2002 and 2017 point features are then created in order to extract built-up areas using the “buffer” function of the raster package. These operations, named morphological closings [ 14 ], are composed of a dilatation followed by an erosion algorithm. They allow linking close by centroids, ignoring small holes and interstices.…”
Section: Script Presentation and Applicationmentioning
confidence: 99%